Research on Power Information Network Attack Detection Method Combining Multiple Kalman Filter Algorithms - Hu, Zheng; Tang, Yong; Gou, Xiang (2023 7th Asian Conference on Artificial Intelligence Technology (ACAIT), 2023)
In order to further improve the attack detection level of power information network, this paper proposes an attack detection method based on improved cubature Kalman filter (ICKF) to detect false data injection attacks. Among them, the cubature Kalman filter algorithm (CKF) is selected as the basic detection algorithm, and it is improved to further improve its detection performance. Simulation results show that compared with other state estimation algorithms, ICKF can estimate the state of power information system more accurately, and its average absolute error is only 2.0124%. In addition, the attack detection method based on ICKF can effectively detect the false data injection attacks. Therefore, the designed detection method based on ICKF can effectively detect false data injection attacks, which further ensures the security of power information, and has certain practical application value.